Uptake, accumulation and elimination of polystyrene microspheres in tadpoles of Xenopus tropicalis. (December 2016) - Hu, Lingling; Su, Lei; Xue, Yingang; Mu, Jingli; Zhu, Jingmin; Xu, Jiang; Shi, Huahong
Abstract: Microplastic is an emerging contaminant affecting freshwater and marine ecosystem across the globe. In the present study, the filter feeding tadpoles of Xenopus tropicalis were exposed to polystyrene microspheres (1 and 10 μm) for 48 h. Microspheres were observed in gills and digestive tract of tadpoles within 1 h after exposure as well as in feces 6 h after exposure. The accumulation of microspheres in the tadpoles were concentration dependent (Univariate ANOVA, p < 0.001), but no time dependent accumulation of microspheres was observed in tadpoles 48 h after exposure (Univariate ANOVA, p > 0.05). After the exposed tadpoles were transferred to clean water, the number of microspheres in the tadpoles decreased dramatically after 1 d and continued to decrease gradually afterwards. The absorbed polystyrene particles in unfed tadpoles was significantly higher than those in the fed tadpoles at 12 and 24 h after exposure. After transfer to clean water, the fed tadpoles showed a significant decrease in the amount of absorbed polystyrene particles, while the unfed tadpoles showed no significant change in the amount of absorbed polystyrene particles. Our results suggested that microspheres were likely to be ingested and egested relatively fast by tadpoles. Our results indicated that aquatic vertebrate organisms might ingest more microplastics if the abundance of microplastics continues to increase while the available food becomes less. Graphical abstract: Highlights: The ingestion of polystyrene microspheres was determined in Xenopus tropicalis tadpoles. Microspheres presented in gills and digestive tract of tadpoles after 1 h exposure. The number of microspheres in tadpoles greatly decreased 1 d after clearance. Food decreased the absorption and increased the elimination of microspheres. Microspheres were likely to be quickly ingested and egested by tadpoles.